The Measurement of Saving, Investment, and Wealth. - Lipsey, Robert E. (Studies in income and wealth., 1989)
There is probably no concept other than saving for which U.S. official agencies issue annual estimates that differ by more than a third, as they have done for net household saving, or for which reputable scholars claim that the correct measure is close to ten times the officially published one. Yet despite agreement among economists and policymakers on the importance of this measure, huge inconsistencies persist. Contributors to this volume investigate ways to improve aggregate and sectoral saving and investment estimates and analyze microdata from recent household wealth surveys. They provide.